2009
DOI: 10.3945/ajcn.2008.27338
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K supplementation and progression of coronary artery calcium in older men and women

Abstract: Phylloquinone supplementation slows the progression of CAC in healthy older adults with preexisting CAC, independent of its effect on total MGP concentrations. Because our data are hypothesis-generating, further studies are warranted to clarify this mechanism. This trial was registered at clinicaltrials.gov as NCT00183001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
194
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(210 citation statements)
references
References 39 publications
7
194
1
5
Order By: Relevance
“…In line with this, supplementing elderly subjects for 3 years with vitamin K1 significantly halted the progression of coronary artery calcification in the group of participants adherent to treatment, supporting our view that improving the vascular vitamin K status positively affects vascular health. 24 Moreover, in subjects with normal renal function, the intake of dietary vitamin K2 was inversely correlated with the Figure 5. Vitamin K2 supplementation reduces dp-ucMGP but not dp-cMGP levels in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, supplementing elderly subjects for 3 years with vitamin K1 significantly halted the progression of coronary artery calcification in the group of participants adherent to treatment, supporting our view that improving the vascular vitamin K status positively affects vascular health. 24 Moreover, in subjects with normal renal function, the intake of dietary vitamin K2 was inversely correlated with the Figure 5. Vitamin K2 supplementation reduces dp-ucMGP but not dp-cMGP levels in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Besides blood coagulation, osteoporosis, and osteoarthritis, it became gradually aware that many physiological and pathological phenomena, such as fertility [36], atherosclerosis [37][38][39], brain development [40], dementia [41], and glucose metabolism [42][43][44], are related to the status of vitamin K sufficiency. We sincerely hope that vitamin K study leads to discoveries of new biological mechanisms and targets for disease prevention and treatment and eventually contributes to human culture and welfare.…”
Section: Resultsmentioning
confidence: 99%
“…This imprecision may have affected the association between lower calcification scores in the presence of higher levels of vitamin K and thus higher levels of cMGP. As far as this is concerned, it is important to realize that it has recently been shown that vitamin K supplementation was associated with slower progression of coronary calcium scores [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on an association between high vitamin K intake and reduced cardiovascular risk or less arterial calcification [12][13][14]. On the contrary, the use of vitamin K antagonists is associated with increased coronary and cardiac valve calcification [15,16].…”
Section: Introductionmentioning
confidence: 99%